Analysis of tragic deaths reflected in Eugene Eunesco’s the lesson - Lariesto, Pioro Benevolent (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2024)
The play titled "The Lesson" by Eugene Eunesco serves as a literary portrayal of inexplicable and jarring modern-day deaths, illustrating the societal complexities, notably poverty-induced suffering and social scorn, that contribute to such tragedies. This analysis, employing library research, delves into the demise of a determined young pupil receiving tutoring from her professor. Initially vibrant and ambitious, she meets an untimely end amid the professor's relentless teaching approach. This narrative unveils the nonsensical realities of contemporary society, where deaths arising from frustration and ridicule prevail. Examples include a student's suicide due to financial constraints and a mother's tragic end alongside her children due to economic strains.